(untitled) (Bangladesh Journal of Medical Science, 2025)
Background The durability and effectiveness of dental restorations are greatly affected by the strength of the dentin bond. Adhesion between dentin and restorative materials may be affected by several cavity preparation processes, including conventional, laser, and air abrasion. Examining how various cavity preparation methods affect dentin bond strength is the goal of this research. Materials and Methods The cavity preparation method was determined by randomly assigning 80 removed human molars to one of four groups: conventional rotary (control), laser, air abrasion, or ultrasonic. After the appropriate procedure was used to prepare each tooth, a composite resin substance with a bonding agent was used to repair it. Specimens were tested for microtensile bond strength after being stored in distilled water for 24 hours. Statistical analysis was performed using one-way ANOVA followed by Tukey’s post hoc test, with a significance threshold of p<0.05. The findings were reported in megapascals (MPa). Results The bond strength values (mean ± SD) for the groups were Group 1 (Conventional rotary): 28.5 ± 4.2 MPa, Group 2 (Laser): 22.3 ± 3.8 MPa, Group 3 (Airabrasion): 25.7 ± 3.6 MPa, Group 4 (Ultrasonic): 27.1 ± 4.0 MPa. Statistical analysis showed that the conventional rotary and ultrasonic groups demonstrated significantly higher bond strengths compared to the laser group (p<0.05). The air abrasion group exhibited intermediate bond strength values, but no significant difference was observed between air abrasion and the other techniques. Conclusion Conventional rotary and ultrasonic techniques provide superior dentin bond strength compared to laser cavity preparation. Air abrasion yields comparable results to conventional methods but did not outperform them. Laser preparation significantly reduces bond strength, suggesting that it may require modified bonding protocols for optimaladhesion. BJMS, Volume: 24. Supplementary Issue 2025, Page : 104-108